A Multispecies Biofilm In Vitro Screening Model of Dental Caries for High-Throughput Susceptibility Testing - Heersema, Lara A. (High Throughput, 2019)
There is a current need to develop and optimize new therapeutics for the treatment of dental caries, but these efforts are limited by the relatively low throughput of relevant in vitro models. The aim of this work was to bridge the 96-well microtiter plate system with a relevant multispecies dental caries model that could be reproducibly grown to allow for the high-throughput screening of anti-biofilm therapies. Various media and inoculum concentrations were assessed using metabolic activity, biomass, viability, and acidity assays to determine the optimal laboratory-controlled conditions for a multispecies biofilm composed of Streptococcus gordonii, Streptococcus mutans, and Candida albicans. The selected model encompasses several of the known fundamental characteristics of dental caries-associated biofilms. The 1:1 RPMI:TSBYE 0.6% media supported the viability and biomass production of mono- and multispecies biofilms best. Kinetic studies over 48 h in 1:1 RPMI:TSBYE 0.6% demonstrated a stable biofilm phase between 10 and 48 h for all mono- and multispecies biofilms. The 1:1:0.1 S. gordonii: S. mutans: C. albicans multispecies biofilm in 1:1 RPMI:TSBYE 0.6% is an excellent choice for a high-throughput multispecies model of dental caries. This high-throughput multispecies model can be used for screening novel therapies and for better understanding the treatment effects on biofilm interactions and stability.